Peran Fasilitator Terhadap Pemberdayaan Perempuan Melalui Pengembangan UMKM Pada Bank BTPN Syariah Di Mms Wonokromo - Nadilla, Rosaiva; Soebiantoro, Ugy (Al-Ijtimā': Jurnal Pengabdian Kepada Masyarakat, 2025)
Mentoring provided by the facilitator in empowering women MSMEs actors is one of the strategic efforts to support economic development, especially among underprivileged communities. Bank BTPN Syariah plays a role not only as a provider of business capital, but also as a partner that provides guidance in improving entrepreneurial skills, business management, and implementing marketing strategies. This research was conducted in the Mitra Mandiri Syariah (MMS) Wonokromo community, which has great economic potential but still requires assistance for business development. The methods used include identifying needs through surveys, SWOT analysis, providing materials, evaluating learning outcomes, direct practice, reporting, and assessing the impact of the program. The focus of assistance includes strengthening business identity, utilizing media for promotion, using digital platforms such as marketplaces, and implementing delivery services. The results of this program show an increase in managerial skills, mastery of marketing strategies, and increasing income of MSMEs actors. Customers who are assisted are more confident in running their businesses with a sustainable approach. This program makes a real contribution to supporting women's empowerment, which is expected to have a positive impact on the welfare of families and society at large.